Analisis Ragam Bahasa Non-Baku dalam Laporan Karya Tulis Ilmiah Siswa Kelas VIII F SMP Negeri 1 Gatak - Risanaya, Risa, Drs. Yakub Nasucha, M.Hum (2017)
The purpose of this research is to describe the process of non-standard language diversity on scientific essay report of VIII F grade students SMP Negeri 1 Gatak and implementing the process of non-standard language diversityin scientific papers reporting on learning Indonesian in SMP Negeri 1 Gatak. The sources of data in this study are archives in the form of written or visual related to the problem in the research that is scientific essay of students. In the collecting data the researcher use see and record technique. The theory that used is non-standard language diversity. Type of this research is descriptive qualitative. The researcher analyze using the interactive analysistechniques. This study shows that the process of non-standard language diversity in the student scientific paper there retwenty-six types of non-standard language diversity contained in the scientific papers students report. Variety of non-standard is Indonesian Language that do not institutionalized and are characterized by traits that deviates from the norm of the standard variety. Data that are not standard in the form of (1) the deviation word formation rules, which appears in the use of incorrect affixes, affixes discharge, the use of non-standard basic form including the use of inaccuracy pronouns, (2) the use of the elements of the callanguage,(3) the use of Malay Betawi dialect, (4) the use of hesitation. Implementation of non-standard diversity language on Indonesian learning in SMP Negeri 1 Gatak.